2016
DOI: 10.1016/j.alit.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms (DIHS/DRESS): 11 years retrospective study in Thailand

Abstract: DRESS is associated with severe morbidity and mortality. Phenytoin, nevirapine, allopurinol, and cotrimoxazole were the major causes. Allopurinol-induced DRESS had the longest onset time, and was associated with higher eosinophilia and incidence of renal involvement. Raising awareness among both health care providers and public for early detection and withdrawal of the causative agent is critical to save life and reduce morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
70
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 29 publications
19
70
3
3
Order By: Relevance
“…The onset of DRESS is approximately 1-8 weeks after drug initiation with the mortality rate of approximately 10% (Criado et al, 2012). From 2004 to 2014, the King Chulalongkorn Memorial Hospital Thailand reported list of drugs that could cause DRESS in Thai patients, including PHT, nevirapine, allopurinol, cotrimoxazole, dapsone, CBZ, isoniazid, ciprofloxacin, clindamycin, dacomitinib, danazol, omeprazole, and sulfadiazine (Hiransuthikul et al, 2016). Abacavir is used for treatment of human immunodeficiency virus type I infection (Sukasem et al, 2014;White et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of DRESS is approximately 1-8 weeks after drug initiation with the mortality rate of approximately 10% (Criado et al, 2012). From 2004 to 2014, the King Chulalongkorn Memorial Hospital Thailand reported list of drugs that could cause DRESS in Thai patients, including PHT, nevirapine, allopurinol, cotrimoxazole, dapsone, CBZ, isoniazid, ciprofloxacin, clindamycin, dacomitinib, danazol, omeprazole, and sulfadiazine (Hiransuthikul et al, 2016). Abacavir is used for treatment of human immunodeficiency virus type I infection (Sukasem et al, 2014;White et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The low nevirapine‐induced SJS/TEN in Asian countries may be related to the frequency of nevirapine use in Asian countries. However, it has been reported that nevirapine can cause more cases of drug reaction with eosinophilia and systemic symptoms complex (DRESS) than SJS/TEN in Thailand . Clinicians still have to be aware of nevirapine‐induced DRESS in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…In every published case series describing these rashes, systemic involvement was noted and mortality rates were high, specifically in TEN and Stevens-Johnson syndrome. 7,15 Howard et al 16 reported a similar situation involving a cancer patient receiving high-dose methotrexate that resulted in toxicity; the patient improved after hemodialysis. Generally, morbidity and fatality in cutaneous adverse diseases is not directly caused by the skin disease but by the complications of organ injury and sepsis, wherein skin denudation allowed microbial entry into the circulation.…”
Section: Discussionmentioning
confidence: 99%